1983
DOI: 10.1007/bf00257340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between impaired parasympathetic and sympathetic cardiovascular control in diabetes mellitus

Abstract: Summary.We have investigated the relationship between vagal and sympathetic lesions in 62 diabetic patients and compared the results with those from 37 healthy subjects. Vagal function was assessed by heart rate changes with forced breathing. Sympathetic control was measured by the heart rate and blood pressure changes after standing and the concomitant plasma catecholamine response. The integrity of the postganglionic sympathetic neuron was evaluated separately by testing sudomotor function. Impaired sympathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 24 publications
2
11
1
2
Order By: Relevance
“…On to the other hand, cardiac sympathetic nerve function was considerably preserved before the marked progression of complications, though it diminished in diabetics as a whole. The present results support the previous reports of Bennett et al (1975), Lloyd-Mostyn et al (1975) and Wieling et al (1983). They used HR variations during deep breathing or to Valsalva maneuver as an index of parasympathetic nerve function, while as an index of sympathetic nerve function, Bennett et al (1975) used the HR increase and the increment of systolic blood pressure 1 or 5 min after standing, and Lloyd- Mostyn and Watkins (1975) used the HR increase 3 min after standing or the HR decrease after the administration of propranolol, and Wieling et al (1983) used the changes of HR and blood pressure, serum catecholamine concentration 5 min after standing.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On to the other hand, cardiac sympathetic nerve function was considerably preserved before the marked progression of complications, though it diminished in diabetics as a whole. The present results support the previous reports of Bennett et al (1975), Lloyd-Mostyn et al (1975) and Wieling et al (1983). They used HR variations during deep breathing or to Valsalva maneuver as an index of parasympathetic nerve function, while as an index of sympathetic nerve function, Bennett et al (1975) used the HR increase and the increment of systolic blood pressure 1 or 5 min after standing, and Lloyd- Mostyn and Watkins (1975) used the HR increase 3 min after standing or the HR decrease after the administration of propranolol, and Wieling et al (1983) used the changes of HR and blood pressure, serum catecholamine concentration 5 min after standing.…”
Section: Discussionsupporting
confidence: 94%
“…Diminished aHR, however, was found only in the patients with long-standing complicated diabetes. Thus, both cardiac parasympathetic and sympathetic nerve function were significantly impaired in the diabetics as compared with the controls and that parasympathetic nerve damage occurred early whereas sympathetic innervation was preserved, diabetic autonomic neuropathy ; heart rate variation The parasympathetic and sympathetic nerve damage in diabetic patients had been investigated in previous reports, and some authors (Bennett et al 1975;Lloyd-Mostyn and Watkins 1975;Wieling et al 1983) Hospital, 13 Maeda parasympathetic nerve damage occurred more earlier than the sympathetic nerve damage and others (Kageyama et al 1979 ;Hilsted 1982) had reported that both parasympathetic and sympathetic nerve damage in diabetics occurred at the same time. Such difference in opinions results from the following reasons : Firstly, the parasympathetic and sympathetic nerve function was evaluated by different indices or responses of different organs, i.e., several heart rate (HR) variations as indices of parasympathetic nerve function, whereas changes in blood pressure, serum catecholamine concentration or serum dopamine-/3-hydroxylase activity as indices of sympathetic nerve function.…”
mentioning
confidence: 98%
“…In the MA group, autonomic tests of heart rate change were more frequently abnormal compared to blood pressure changes to posture and hand grip. Previous studies suggest that this indicates parasympathetic (vagal) rather than sympathetic neuropathy [25,26]. Heart rate measurements taken before, during, and after adopting the supine position showed higher rates in those with MA, although this was only significant when comparing supine pulse rates.…”
Section: Discussionmentioning
confidence: 75%
“…Prior to inclusion in the present study, all subjects underwent cardiovascular autonomic function testing. Parasympathetic control of HR (heart rate) was evaluated by quantifying the timecourse and magnitude of HR responses to active standing and the Valsalva manoeuvre [21][22][23]. Sympathetic cardiovascular control was assessed by the BP responses to active standing and the Valsalva manoeuvre [19,24].…”
Section: Subjects and Study Designmentioning
confidence: 99%